2002
DOI: 10.1348/147608302169517
|View full text |Cite
|
Sign up to set email alerts
|

Lessons from psychotherapy research for psychological interventions for people with schizophrenia

Abstract: This article argues that psychological interventions for people with schizophrenia could be developed by being informed by research from the wider psychotherapy literature. We specifically argue that research on these interventions has ignored two key themes from this wider literature: first, the contention that differing models of intervention broadly result in similar outcomes, known as the 'equivalent outcomes paradox'; and second, the phenomenon of 'investigator allegiance' whereby the conclusions that may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 49 publications
1
35
0
Order By: Relevance
“…The importance of integrating consumers in health services research is widely recognised and has potential benefits for policy making, research, practice, improved implementation, better care and better health (12,13). When developing and evaluating complex interventions, it is necessary to establish some degree of acceptability to those who may benefit from it and to explore the context in which it is delivered (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of integrating consumers in health services research is widely recognised and has potential benefits for policy making, research, practice, improved implementation, better care and better health (12,13). When developing and evaluating complex interventions, it is necessary to establish some degree of acceptability to those who may benefit from it and to explore the context in which it is delivered (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have concluded that psychodynamic psychotherapy is clearly not effective in schizophrenia and that it may possibly be unhelpful (Mueser and Berenbaum, 1990). Paley and Shapiro (2002), when discussing the relative merits of different types of therapy in the treatment of psychosis argue that there may be an 'equivalence paradox' in relation to outcome from therapy across disorders i.e. that different therapies generally produce equivalent outcomes.…”
Section: Psychological Treatment Approaches In Schizophreniamentioning
confidence: 99%
“…A combination of cognitive interventions alongside psychodynamically orientated trauma-focused therapy has also proven to be successful in reducing psychotic experiences (Read and Argyle, 1999;Paley and Shapiro, 2002). This, however, has become contentious (Tarrier et al, 2002).…”
Section: Approaches Treatments and Interventionmentioning
confidence: 99%